Zoneamento ambiental do município de Querência - MT - Rossete, Amintas Nazareth (Universidade Federal de São Carlos, 2008)
The sustainable use of the natural resources should be a basic premise to be integrated in environmental policies in order to avoid the growing natural ecosystems destruction. To assure a better appropriation of these resources is fundamental to apply the territorial arrangement landscape, with the formulation of environmental zonings. The municipality of Querência is located on Xingu River Basin, in the Northeast of Mato Grosso State, an Amazonian region knowledge as the arch of deforestation , in which has been registered the increase of clearing areas for farming and pasture in the last 20 years. The aim of this work is the environmental characterization and the elaboration of an environmental zoning of Querência municipality, starting from the definition and recognizing of different types of landscapes and land use, on the study area. The environmental inventory of the main environmental variables, that compose landscape, was made through field work and based on information processing in digital format of the thematic maps: planialtimetric, geology, geomorphology, pedology, agricultural suitability, vegetation and deforestation. Using geographical information systems - ArcGis 9.2 and SPRING 4.2 it was elaborated the land use and land cover maps obtained from CBERS II satellite (2006), as well as overlays operations that made possible the definition of landscape units, and resulted in the elaboration of the environmental zoning of Querência municipality. It was set up six zones: Preservation of Hydric Resources, Urban Use, Intensive Use, Forest Management, Protected Areas and Multiple Use.
Keywords: Zoneamento ambiental; Ecologia da paisagem; Geoprocessamento; Querência (MT); CIENCIAS BIOLOGICAS::ECOLOGIA